Knowledge, Attitudes, and Practices of Military Personnel Regarding Heat-Related Illness Risk Factors: Results of a Chinese Cross-Sectional Study - Wang, Xuren; Xia, Demeng; Long, Xisha; Wang, Yixin; Wu, Kaiwen; Xu, Shuogui; Gui, Li (Frontiers in Public Health, 2021)
Background: Military personnel are widely exposed to risk factors for heat-related illnesses. Knowledge, attitudes, and practices (KAP) are 3 of the most important means by which to prevent such illnesses, but there has been a lack of investigations into and correlation analyses of KAP. This study aimed to explore the heat-related KAP of military personnel in China. Methods: We conducted a cross-sectional study in June 2019. A total of 646 military personnel were recruited from two Chinese Navy troops in the tropical zone and one troop in the temperate zone. We collected data on demographic characteristics and KAP scores using questionnaires. Univariate analysis and Scheffe’s method were used for data analyses. Results: The mean KAP scores were 10.37 (range = 3–13, standard deviation = 1.63) for knowledge (K-score), 7.76 (range = 0–16, SD = 2.65) for attitudes (A-score), and 3.80 (range = 1–6, SD = 1.12) for practices (P-score). There were noticeable differences in mean K-score according to age, military rank, and educational level (P < 0.05). Participants from the tropical zone had higher A-scores (P < 0.05) and higher P-scores (P < 0.001) than those from the temperate zone. Additionally, participants with relevant experience also had higher A-scores (P＜0.05) than those without such experience. Conclusions: Military personnel’s awareness of preventive and first-aid measures against heat-related illnesses need to be strengthened. It will be very important to develop educational programmes and enrich systematic educational resources to raise this awareness.